2017
DOI: 10.1002/aoc.4042
|View full text |Cite
|
Sign up to set email alerts
|

Adamantyl ferrocene derivatives: Antioxidant abilities and effects on model lipid membranes

Abstract: A series of homoannularly and heteroannularly substituted adamantyl ferrocene derivatives has been synthesized and their effects on membrane fluidity were investigated using liposomes as the membrane models. The liposome formulations of adamantyl ferrocene derivatives were characterized by using dynamic light scattering, differential scanning calorimetry and fluorescence anisotropy measurements. It was demonstrated that adamantyl ferrocene derivatives incorporated into the liposome significantly affect the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…18−21 For example, the ailanthoidol ferrocene shows good radical scavenging activity (RSA) for AAPH • (2,2′-azobis(2-amidinopropane)dihydrochloride) and ABTS •+ (2,2-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid) radicals, 19 while the adamantyl ferrocene was reported with certain antioxidant activity toward the DPPH • (1,1-diphenyl-2-picrylhydrazine) radical. 20 In addition, many studies have shown that the accumulation in a long period of oxidative stress, that is, reactive oxygen species (ROS) and reactive nitrogen species (RNS), leads to diseases such as diabetes, hypertension, and cancers. 22−24 The elimination of ROS or RNS together with the protein binding capacity is a good approach to preliminarily evaluate the antioxidant and anticancer activity of potential metallodrugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18−21 For example, the ailanthoidol ferrocene shows good radical scavenging activity (RSA) for AAPH • (2,2′-azobis(2-amidinopropane)dihydrochloride) and ABTS •+ (2,2-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid) radicals, 19 while the adamantyl ferrocene was reported with certain antioxidant activity toward the DPPH • (1,1-diphenyl-2-picrylhydrazine) radical. 20 In addition, many studies have shown that the accumulation in a long period of oxidative stress, that is, reactive oxygen species (ROS) and reactive nitrogen species (RNS), leads to diseases such as diabetes, hypertension, and cancers. 22−24 The elimination of ROS or RNS together with the protein binding capacity is a good approach to preliminarily evaluate the antioxidant and anticancer activity of potential metallodrugs.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the oxidation of ferrocene to ferrocenium cations and the reversible reduction process are reported to be feasible in biological systems and are very useful in the free radical scavenging processes as they can eliminate several harmful free radicals such as HO • and O 2 •– . Recent studies also demonstrated the use of the ferrocene derivatives as a structural feature in antioxidants. For example, the ailanthoidol ferrocene shows good radical scavenging activity (RSA) for AAPH • (2,2′-azobis­(2-amidinopropane)­dihydrochloride) and ABTS •+ (2,2-azino-bis­(3-ethylbenzothiazoline)-6-sulfonic acid) radicals, while the adamantyl ferrocene was reported with certain antioxidant activity toward the DPPH • (1,1-diphenyl-2-picrylhydrazine) radical . In addition, many studies have shown that the accumulation in a long period of oxidative stress, that is, reactive oxygen species (ROS) and reactive nitrogen species (RNS), leads to diseases such as diabetes, hypertension, and cancers. The elimination of ROS or RNS together with the protein binding capacity is a good approach to preliminarily evaluate the antioxidant and anticancer activity of potential metallodrugs.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrocene and adamantane are chemically very different but are quite similar in size and hydrophobicity, and the results obtained in these studies open wide possibilities for applications of adamantly ferrocene derivatives. In an article, Stimac and colleagues synthesized and reported the antioxidant potential of ferrocene derivatives through the DPPH free radical scavenging method [147]. The percentage of DPPH quenching in the presence of Fc-COOH and all prepared compounds was measured and shown in a graph exposing that monosubstituted compounds 156 and 158 exhibited better antioxidant potential than disubstituted compounds 157 and 159 (Figure 56).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The group of Bano and Khan recently conducted a detailed study of ferrocenegrafted acyl urea derivatives and homoleptic carboxylates through in silico and in vivo analysis and evaluated their antidiabetic potential [147]. All examined scaffolds showed…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Milaeva et al showed that the antioxidant activity of ferrocene containing 2,6-di-tert-butylphenol or phenyl groups strongly depends on the presence of a phenolic group but is enhanced in the presence of the ferrocenyl fragment [21]. Štimac et al synthesized a series of homoannularly and heteroannularly substituted adamantyl ferrocene derivatives, which showed antioxidant activity in the DPPH assay and protected the cell membrane from peroxidation [22].…”
Section: Introductionmentioning
confidence: 99%